Production Of Biodiesel From Waste Cooking Oil Using Sulfated Tin Oxide Catalyst - Lam , Man Kee (2010)

(untitled)
Biodiesel is a renewable, biodegradable and non-toxic fuel which can be easily produced through transesterification reaction. However, current commercial usage of refined vegetable oils for biodiesel production is impractical and uneconomical due to high feedstock cost and priority as food resources. Low-grade oil, typically waste cooking oil can be a better alternative; however, the high free fatty acids (FFA) content in waste cooking oil does not allow efficient production of biodiesel via current commercial homogeneous transesterification process. Therefore, in the present study, superacid sulfated tin oxide catalyst, SO4 2-/SnO2 has been prepared using impregnation method for biodiesel production via heterogeneous transesterification process.